2011
DOI: 10.1159/000326084
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peripheral Opioid µ-Receptors in Blood Vessel May Lower Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Background/Aims: The role of opioid receptors in the regulation of vascular function remains unclear. In the current study, we evaluated the ability of loperamide, a peripheral opioid receptor agonist, to regulate blood pressure in spontaneously hypertensive rats (SHRs) and examined the mechanism(s) by which loperamide exerts its effects. Methods: In male SHRs, mean arterial pressure (MAP) was measured and hemodynamic analysis was recorded. Additionally, the isometric tension of aortic rings isolated from SHRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 93 publications
2
19
0
Order By: Relevance
“…The hypotensive action of morphine is long established (Cox 1988;Siren and Feuerstein 1992). More recently, both morphine and stimulation of peripheral µ receptors with loperamide was reported to decrease blood pressure in SHR (Chen et al 2011, Mahinda et al 2004. Also endogenous endorphins with affinity for µ receptors were reported to induce hind limb vasodilatation (Champion et al 1997), in agreement with our present finding of decreasing iliac vascular resistance, both after morphine and after biphalin.…”
Section: Biphalin and Morphine Effects In Shrsupporting
confidence: 90%
See 2 more Smart Citations
“…The hypotensive action of morphine is long established (Cox 1988;Siren and Feuerstein 1992). More recently, both morphine and stimulation of peripheral µ receptors with loperamide was reported to decrease blood pressure in SHR (Chen et al 2011, Mahinda et al 2004. Also endogenous endorphins with affinity for µ receptors were reported to induce hind limb vasodilatation (Champion et al 1997), in agreement with our present finding of decreasing iliac vascular resistance, both after morphine and after biphalin.…”
Section: Biphalin and Morphine Effects In Shrsupporting
confidence: 90%
“…It may differ from the final official version of record. 14 peripherally acting µ-receptor agonist, did not alter the cardiac output in anesthetized SHR (Chen et al 2011). Thus, any substantial contribution of a decrease in cardiac output to biphalin's hypotensive effect remains uncertain.…”
Section: Biphalin and Morphine Effects In Shrmentioning
confidence: 92%
See 1 more Smart Citation
“…The activation of mast cell degranulation by codeine may, therefore, occur through its actions at the opioid receptor [51]. There are 3 recognized types of opioid receptors, namely, mu (μ), delta (δ), and kappa (κ) [53,54]. It has been demonstrated that human mast cells express mRNA for δ- and μ-receptors but not for κ-opioid receptors [51].…”
Section: Drug-induced Pseudoallergymentioning
confidence: 99%
“…The endothelium was removed by gently rubbing it against the teeth of a pair of forceps. Successful removal of the endothelium was confirmed by histological identification and failure of 1 µmol/L acetylcholine to relax the rings that had been pre-contracted with potassium chloride as described previously [10]. …”
Section: Methodsmentioning
confidence: 99%